Simulation Analysis of Benchmark Axial Velocity After Sudden Expansion using Computational Fluid Dynamics - Onah, T. O.; Egwuagu, O. M.; Ozioko, R. E.; Chukwujindu, S.; Nwankwo, A. M.; Nnaji, I. A.; Aka, C. C. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2022)
Computational Fluid Dynamics (CFD)- ANASYS 2020R1 was used for the analysis of food and drug administration (FDA) benchmark study for biomedical flow transition. An idealized medical device is presented within this study and the CFD predictions of pressure and velocity are compared against experimental measurements of pressure and velocity. The fluid flow transition considered for Reynold numbers(s) 500, 2000, and 6500 with turbulent fluid flow models- laminar, k-omega, k-omega SST and k-epsilon based on throat Reynolds number Reth. 500, 2000 and 6500. Mesh independence K-omega SST model used at 0.0008, 0.0004 and 0.0002 element sizes showed good matched velocity of 5.9m/sec. This converged at 0.0002, which is 2% of total pressure drop. Axial velocity at centreline for Reth 500, 2000 and 6500 at line X =0, showed maximum difference of 77.4% velocity centerline at 0.08m and 19% wall pressure at -0.09m sudden expansion laminar region of Re = 500. Besides, 65.6% and 17.2% obtained at transition Re =2000, showed good agreement between CFD simulations and experimental measurements, at turbulent region Re = 6500, all models were in good agreement at 49.6% velocity centerline and 8.10% pressure drop in laminar region. Also, downstream of the simulation of Reth =6500, other models disappeared which demonstrated K-epsilon model is best at higher Reynolds region. The result revealed negligible pressure gradient at the center line of the wall pressure, and dropped at the normalization point of the experimental pressure data range of 0 to -120n/m2 and balanced at the throat Reynolds number of Reth = 500.